SOKKIE DANCING IN PRETORIA: POPULAR AFRIKAANS MUSIC, DANCE, AND IDENTITY - Holtzhausen, Cornelius A. (International Library of African Music, 2020)
Afrikaans protest music influenced by rock has received a substantial degree of academic attention in recent years. While significant, the emphasis on Afrikaans protest music has left Afrikaans pop music largely unexamined. As this genre enjoys wide popularity amongst Afrikaners, this article considers this lacuna in academic inquiry. Afrikaans pop music is widely consumed in South Africa and is a major part of its music industry. In this article, I bring into focus how a strand of music, that might seem to avoid meaningful dialogue through superficial lyrics, forms part of an Afrikaner subculture and a strategy to preserve identity, norms, and values. In particular, I argue for a wider contextual understanding of music and the limitations of lyrical analysis to produce meaningful insight into music’s role in enabling participants to negotiate identity and place. Drawing on fieldwork conducted at Presley’s, a night club in Pretoria, I elucidate this process through the dialogue between Afrikaans music and sokkie dance.
Keywords: Music; Dance; South Africa; Ethnomusicology; Afrikaans; Pretoria; Pop Music; Sokkie Dance; Identity; Protest Music; African Music